2004
DOI: 10.1111/j.1600-6135.2004.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic organ transplantation

Abstract: This article presents an overview of factors associated with thoracic transplantation outcomes over the past decade and provides valuable information regarding the heart, lung, and heart-lung waiting lists and thoracic organ transplant recipients. Waiting list and post-transplant information is used to assess the importance of patient demographics, risk factors, and primary cardiopulmonary disease on outcomes.The time that the typical listed patient has been waiting for a heart, lung, or heart-lung transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…Both the latter organs suffer the disadvantage of having ongoing exposure to the environment, thus they strongly rely on their organ-specific innate immunity for protection from the environmental noxious agents (46)(47)(48)(49). Important components of the lung-specific innate immune defense mechanisms are provided by pulmonary surfactant phospholipids and the pulmonary surfactant associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Both the latter organs suffer the disadvantage of having ongoing exposure to the environment, thus they strongly rely on their organ-specific innate immunity for protection from the environmental noxious agents (46)(47)(48)(49). Important components of the lung-specific innate immune defense mechanisms are provided by pulmonary surfactant phospholipids and the pulmonary surfactant associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing interest in determining the impact of lung transplantation on functional status and QOL in patients with advanced lung disease (7)(8)(9). Preliminary studies employing standardized QOL questionnaires have reported significant short-and intermediate-term improvements in various QOL measures following lung transplantation (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…For example, over 50% of human cardiac allograft recipients and 80% of lung recipients exhibit chronic rejection within 10 years. Recent additions to the clinical immunosuppressive armamentarium, such as blocking (1) or depleting antibodies (2) and pharmacologic inhibitors (3), have had little appreciable impact on this phenomenon (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%